(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2025)
Considering the substantial impact of St. Augustine’s stances on the evil in the world, the status and the actions of the devil, and the dangers of collaborating (or compacting) with the dark forces on the development of the medieval theology of violent reckoning against the evil, this text examines one aspect of his use of the motif of the fall of the angels in the analysis of the problem and the proliferation of evil. As one of the last early Christian authors who uses elements from the story from the Biblical tradition and the tradition around the fallen Watchers from the First Book of Enoch, St. Augustine approaches the problem of evil from the standpoint of the importance of free choice and of the intentional transgression. The text first offers a brief overview of the conception of the evil in the Manichean cosmogony, in order to introduce the positions to which St. Augustine explicitly opposes. The important role of the primordial sin according to him is shown, and especially, the status of the devil as a sinner from the beginning, or as a self-determined rebel against God. Тhe ideas on the origin of evil through the role of the satan are outlined through St. Augustine’s polemic against the Manicheans. The majority of the text is devoted to the problem of the angelic (non)blessedness. St. Augustine’s position on the existence of two groups of heavenly beings (good and evil) is shown, as is the idea about the awareness, or foreknowledge, of a potentially undisturbed eternal bliss, as opposed to the ignorance (or the foreknowledge) about the loss of this perennial happiness as a result of the intentional apostasy of the bad angels. These few aspects of St. Augustine’s complex theology trace his underlying position on the importance of the conscious choice to constantly be(come) better and to imitate God, despite man’s initial sinfulness.